Implementation of Character Education Through Occupational Safety and Health (OSH) Training on Personal Protective Equipment (PPE) for Vocational School Students - Yuliani, Euis Nina Saparina; Hernadewita; Rahmi, Syifa Ur (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
SMKN 1 Gunung Sindur contributes significantly to the preparation of vocational students with the technical and professional competencies required by industry. To improve this effort, it works together with Universitas Mercu Buana on a community service program that integrates character education with occupational safety and health (OSH), focusing on how to properly use personal protective equipment (PPE). The program is in line with the key performance indicators for higher education, which help build stronger partnerships between higher education institutions and vocational schools. Activities were designed from an industrial engineering perspective, emphasizing ergonomics, safety management, and a safety-oriented work culture, delivered through interactive training, video demonstrations, and structured discussions. Program outcomes were evaluated by using a post-training questionnaire (P1–P5). The results showed that 70.5% of students had not previously received similar training; 97% perceived the materials as highly beneficial; 91% found the content easy to understand; 90% reported engaging delivery; and 82% considered the training duration sufficient. Overall, the program improved students’ understanding and correct practice of PPE application, strengthened OSH awareness, and fostered positive attitudes towards safe work behavior. This initiative supports graduate employability and provides a practical model for sustainable collaboration between higher education institutions and vocational schools.